LEİBNİZ VE KÖTÜLÜĞÜN KAYNAĞI - Veli Urhan (Felsefe Dünyası)
It has no any doubt that problem of devil is of great importance for atheistic thought systems as well as theistic ones. Leibniz seriously treats and gives a large room to the problem focused on the source and nature of evil in his famous work called "Théodicéé" as just many philosophers reasoned upon the existence of God and his relationship with the universe did try to find a solution before him. To Leibniz, the source of evil takes place in the understanding of God. Leibniz, having the idea of that God always prefer the best in his doings, asks how and with what God establishes the borders of the good if evil doesn't exist; and thus achieves these conclusion: it is inevitable to create goodness and evil together.